EXPLOITATION OF GEOSITES IN TOURISM DEVELOPMENT, THE CASE OF GHAR DJEMAA WILAYA OF GUELMA - Amina Benelmadjat; Lamia Bouldjemar; Bitat Belkacem (International Journal of Innovative Technologies in Social Science, 2024)
Geotourism is based on three fundamental principles: education, conservation and sustainable development. Geotourism promotes natural sites such as caves by encouraging their preservation through appropriate facilities (walkways, lighting and regulation of visits) designed to maintain their climatic and geological stability. This article highlights the Ghar Djemaa cave in Guelma, a geological, historical and scientific gem that is still under-exploited. It highlights the urgent need to design appropriate facilities to protect this exceptional heritage, while boosting the local economy and ensuring that it is passed on to future generations.